2002
DOI: 10.1159/000065067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cisplatin Resistance in Clear Cell Carcinoma of the Ovary

Abstract: Resistance of clear cell carcinoma (CCC) of the ovary to platinum-based chemotherapy is associated with a poor prognosis. However, the mechanism underlying the resistance of CCC to platinum has not yet been understood. We conducted the present study to clarify the mechanism of cisplatin (CDDP) resistance in CCC cells. Eleven CCC and 5 serous adenocarcinoma (SAC) cell lines were used in this study. The IC50 to CDDP ranged from 1.3 to 18.0 µM for CCC cells and from 2.2 to 13.0 µM for SAC cells. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…Conversely, given the mitogenic effect of cyclin E and the increase in the proportion of cells in S phase in cyclin E overexpressing cells, drugs that cause DNA damage may have greater efficacy. In ovarian carcinoma, the response to cisplatin therapy has been linked to the proliferative rate of the tumor (Kolfschoten et al, 2000;Itamochi et al, 2002); tumor cells with high S phase have increased sensitivity to cisplatin treatment (Kolfschoten et al, 2000;Itamochi et al, 2002). Additionally in vitro pharmacologic studies have demonstrated that cyclin E overexpression enhances the cytotoxicity of cisplatin/taxol combination therapy in a panel of different solid tumor cell lines (Smith and Seo, 2000) and that abrogation of the G1/S checkpoint may be involved in increasing the efficacy of cisplatin in ovarian cancer cells (Pestell et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, given the mitogenic effect of cyclin E and the increase in the proportion of cells in S phase in cyclin E overexpressing cells, drugs that cause DNA damage may have greater efficacy. In ovarian carcinoma, the response to cisplatin therapy has been linked to the proliferative rate of the tumor (Kolfschoten et al, 2000;Itamochi et al, 2002); tumor cells with high S phase have increased sensitivity to cisplatin treatment (Kolfschoten et al, 2000;Itamochi et al, 2002). Additionally in vitro pharmacologic studies have demonstrated that cyclin E overexpression enhances the cytotoxicity of cisplatin/taxol combination therapy in a panel of different solid tumor cell lines (Smith and Seo, 2000) and that abrogation of the G1/S checkpoint may be involved in increasing the efficacy of cisplatin in ovarian cancer cells (Pestell et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin was chosen for these studies as this is commonly used in the treatment of ovarian cancer and ovarian tumor response to cisplatin has been correlated with proliferative rate (Itamochi et al, 2002). We sought to directly test this hypothesis in our isogenic model (Figure 6).…”
Section: Mdah-2774 T1 Clones Are More Sensitive To Cisplatin Cytotoximentioning
confidence: 99%
“…However, clear cell adenocarcinoma has a poorer prognosis than serous carcinoma (2), and the response rate to platinum-based chemotherapy in patients with clear cell adenocarcinoma is significantly lower than that in patients with serous adenocarcinoma (1). The doubling time for clear cell adenocarcinoma cells is significantly longer than that for serous adenocarcinoma cells (3). Clinically, several characteristics distinguish clear cell adenocarcinoma from the other histological types of epithelial ovarian carcinoma, including high frequency of associated endometriosis, resistance to chemotherapy and poor prognosis even in early stage of disease.…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of clear-cell tumours among epithelial ovarian cancers is around 10%. Clear-cell tumours tend to be resistant to platinumbased chemotherapy, giving rise to a poor prognosis (Itamochi et al, 2002).…”
mentioning
confidence: 99%